The effects of human resource management practices on teacher educator development in Bangladesh: ICT skills and career planning as moderators - Islam, Md. Motaharul (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2018)
Education itself aims at the improvement of human resources (Merwe & Carel, 2012). When researcher talk of HRM practices in teacher educator development, it talk about the development of those human resources who involved in teaching in teacher training colleges. This study comprised teacher educators who are in teaching and working in teacher education or training colleges or working as educational administrators in Bangladesh. Darling-Hammond (2010) thoughts that, development of all categories of people becomes extremely important as the effectiveness of teacher education depend upon how well they perform their roles. People at different levels and performing different roles require different competencies to be effective in their roles (Han & Boulay, 2013). These competencies are also changing from time to time as the environment is changing and knowledge base is continuously improving.